2014
DOI: 10.1002/tie.21651
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Organizational Capabilities and Corporate Entrepreneurial Processes: The Case of Chinese Automobile Firms

Abstract: Corporate entrepreneurship (CE) has contributed to the rapid growth of emerging-market fi rms (EMFs),is how EMFs build and develop organizational capabilities to achieve CE transformation, considering the volatile institutional environment in which they operate, as a way to catch up with their global competitors. This underexamined research question is hence the focus of our study.In the present study, we investigate CE through a stage model that involves initiation, development, and implementation (Russell, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 92 publications
0
24
0
Order By: Relevance
“…On the one hand, export entrepreneurial orientation (EO) is often conceptualized to be reflective of a firm's general proclivity to discover/identify and exploit new export market opportunities (Boso, Cadogan, & Story, ), and, as such, it has been central to the international entrepreneurship thinking (Coviello, McDougall, & Oviatt, ; Covin & Miller, ). Extant research shows that variation in a firm's entrepreneurial orientation causes changes in its export market performance (e.g., Guo, Jiang, & Yang, ; Kuivalainen et al, ; Zhang, Ma, & Wang, ). On the other hand, export market orientation (MO) is viewed as a central tenet of the export marketing thought as it entails implementation of the marketing concept in export markets (Cadogan et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the one hand, export entrepreneurial orientation (EO) is often conceptualized to be reflective of a firm's general proclivity to discover/identify and exploit new export market opportunities (Boso, Cadogan, & Story, ), and, as such, it has been central to the international entrepreneurship thinking (Coviello, McDougall, & Oviatt, ; Covin & Miller, ). Extant research shows that variation in a firm's entrepreneurial orientation causes changes in its export market performance (e.g., Guo, Jiang, & Yang, ; Kuivalainen et al, ; Zhang, Ma, & Wang, ). On the other hand, export market orientation (MO) is viewed as a central tenet of the export marketing thought as it entails implementation of the marketing concept in export markets (Cadogan et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…We extend this existing theorization by suggesting that RTC is a vehicle through which EO and MO influence export performance. Second, while extant export strategic orientation research tends to focus on empirical examination of export strategic orientations in a single‐country study, often in Western advanced economies (e.g., Cadogan et al, ; Kuivalainen et al, ), this study draws on notable studies (e.g., Guo et al, ; Zhang et al, ) to bring on board a developing‐economy market perspective to provide a more complete understanding of how EO and MO are related to export performance (Fang & Zou, ). Accordingly, this study enhances external validity and generalization of export strategic orientation research by testing the proposed theoretical framework (see Figure ) on cross‐national data sets from the United Kingdom and Nigeria.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Roy and Khokle's () case study of international joint ventures identified the stages of sensing and sizing as fundamental in allowing firms to build dynamic capabilities, while reconfiguring/transforming was incorporated within seizing. In their case of the Chinese automotive industry, Guo, Jiang, and Yang () provide a different perspective to the development of dynamic capabilities. Indeed, Guo et al () concluded while institutional endowments manifested through government support might enable firms' rapid startup of entrepreneurial activities, they may also stifle their development and potentially their dynamic organizational capabilities.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Corporate venturing can be divided into internal and external venturing (Phan, Wright, Ucbasaran, and Tan, 2009 In short, CE requires organizations to engage in activities that continuously extend their domain of competence and respond to risks and opportunities through resource configuration and capability development to meet changing customer demands and competitor strategies (Guo et al, 2014). However, CE activities do not occur in a vacuum and are under the influence of institutional environments.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Following these government initiatives, Chinese auto firms, for example, Chang'an in our recent case study (Guo et al, 2014), identified building an independent innovation system as an important entrepreneurial endeavor. The innovation systems were built to develop core technologies, reconfigure available resources, and eventually new products-important CE transformation through innovation and continuous strategic renewal.…”
Section: Recent Transformation Stage (2006-present)mentioning
confidence: 99%